Anxiety of Warriner in Charles Williams’ Dead Calm - Kurniasari, Atika Rahma; Thoriqussuud, Muhammad; Amiq, Amiq; Mufid, Nur; Fanani, Abu (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
Dead Calm is a novel of anxiety undergone by the main character, Warriner, after lacking emotional desires. The mere cause of the emotional desire lack is the hostile incident as well as pain. Therefore, the researcher gets interested in conducting analysis because emotional desires make human life stable. How the main character experiences the anxiety becomes the focus of the researcher’s study. Anxiety’s types as well as descriptive qualitative method are worth using because the researcher is able to observe deeply about anxiety’s symptoms undergone by the main character that is neurotic, moral, and realistic anxiety. Then, the study shows that the main character undergoes those mentioned types of anxiety through his feeling of weakness, worriedness, and punishment fear, remorseful to the other character and facing a real danger. Eventually, the kinds of anxiety deserve a deep studying since people can keep the anxiety out of their life through the knowledge.